Ethnobotanical utilization and cultural significance of taro (Colocasia spp.) in Berau District, East Kalimantan, Indonesia - LINDA OKTAVIANINGSIH; NABILA WULANDARI; DWI SUSANTO; MUHAMMAD FAUZI ARIF (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Oktavianingsih L, Wulandari N, Susanto D, Arif MF. 2025. Ethnobotanical utilization and cultural significance of taro (Colocasia spp.) in Berau District, East Kalimantan, Indonesia. Biodiversitas 26: 5458-5467. Taro (Colocasia spp.) is a tuber crop of the Araceae family valued for its high nutritional and medicinal properties, widely distributed across tropical and subtropical regions. Indonesia, particularly Kalimantan, harbors rich taro diversity and a long history of its utilization. However, comprehensive ethnobotanical studies on taro remain limited, especially concerning varietal diversity, plant parts used, processing methods, and cultural contexts. This study aimed to identify taro varieties in Berau District, East Kalimantan, and document their utilization by different ethnic groups. Data were collected through exploratory surveys, field observations, and semi-structured interviews involving approximately 50 informants from 14 ethnic groups across 26 villages in 10 sub-districts. Twenty accessions belonging to Colocasia esculenta var. esculenta and C. e. var. antiquorum were recorded, thriving in diverse habitats such as home gardens, swamps, and roadsides. Plant parts utilized included tubers (64%), stems (27%), leaves (6%), leaf stalks (2%), and leaf tips (1%). Taro served multiple purposes: staple food and vegetables, ceremonial materials (e.g., natural nail dye for weddings), traditional remedies for skin irritation, and livestock feed. Common preparation methods comprised frying, boiling, sautéing, and steaming. Women constituted the majority of users (92%), predominantly homemakers (60%), with most consumers aged 41-50 years. This study represents the first comprehensive ethnobotanical documentation of taro in Berau, highlighting its cultural and nutritional significance. The findings emphasize the urgency of preserving traditional knowledge to support germplasm conservation, local food innovation, and food security enhancement in tropical regions.